2020
DOI: 10.1002/ecs2.3030
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of experimental environmental change on soil micro‐arthropod communities

Abstract: Global change experiments such as experimental warming and nutrient addition strongly affect the structure and functioning of high latitude and altitude ecosystems. However, it is often unknown to what extend such effects are permanent or whether changes persist after environmental conditions return to pre‐treatment levels. In this study, we assess the legacy effects of temperature manipulation and nutrient addition experiments on alpine soil micro‐arthropod (i.e., Collembola and Oribatida) communities nine ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Although some studies have focused on the effects of warming on soil fauna, the response of soil fauna in high-latitude wetlands to warming is still lacking [ 48 ]. Such research is significant because soil fauna control many soil processes and are connected to aboveground vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have focused on the effects of warming on soil fauna, the response of soil fauna in high-latitude wetlands to warming is still lacking [ 48 ]. Such research is significant because soil fauna control many soil processes and are connected to aboveground vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall and taxon-specific shifts in soil microarthropods at the SPRUCE site suggest treatment effects are taking time to emerge, and possibly leading to greater heterogeneous communities under warming. At the same time, Roos et al (2020) found that the negative effects of warming on collembolan and oribatid community composition persisted even after 9 years after the experimental treatment ended, suggesting shifts in microarthropod composition as long-lasting and potentially not reversible. The work presented here is one component of larger results emerging from the SPRUCE experiment that suggest belowground biodiversity and ecosystem function are altered under warming.…”
Section: Discussionmentioning
confidence: 85%
“…Nine years after cessation of the treatments, Roos et al (2020) found persistent legacy effects of nutrient additions on Collembola and Oribatida community composition, while their abundance had recovered to control levels. In contrast to vegetation (Olsen and Klanderud, 2014b), the presence of herbivores did not consistently affect recovery rates of soil arthropod communities (Roos et al, 2020).…”
Section: Communities and Species Interactionsmentioning
confidence: 97%
“…Nutrient addition had little effect on other taxa such as Diptera (larvae), but Arctorthezia cataphracta (Coccoidea) decreased in abundance in concert with decreases in its host plant (D. octopetala) abundance, indicating that nutrient addition affects the system across trophic levels (Hågvar and Klanderud, 2009). Nine years after cessation of the treatments, Roos et al (2020) found persistent legacy effects of nutrient additions on Collembola and Oribatida community composition, while their abundance had recovered to control levels. In contrast to vegetation (Olsen and Klanderud, 2014b), the presence of herbivores did not consistently affect recovery rates of soil arthropod communities (Roos et al, 2020).…”
Section: Communities and Species Interactionsmentioning
confidence: 99%
See 1 more Smart Citation